2022
DOI: 10.52794/hujpharm.1024991
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Rational Drug Use Awareness of University Students

Abstract: Non-rational drug use harms both health and the economy. This study aims to evaluate the rational drug use awareness of undergraduate students studying in two faculties where future health professionals are trained. The study was carried out with 449 undergraduate students studying at Karadeniz Technical University (KTU) Faculty of Health Sciences and Faculty of Pharmacy. As a data collection tool, the "Consciousness Scale Towards Rational Drug Use (CRDU) in Adults" was developed by Aktas and Selvi. The descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the study conducted by Kartal, Karakas and Kapıkıran (2023), a difference was found between the variables of education level, but no difference was found between the variables of age and gender. In the study conducted by Yeşildağ, Ağırbaş, and Yılmaz (2022), a difference was found between the variables of gender and the department they studied, while no difference was found between the variables of class regular drug use. In the study conducted by Arslan and Ergün (2022) on students, a difference was found between gender variables, but no difference was found between the variables of chronic illness status and drug use status.…”
Section: Discussionmentioning
confidence: 88%
“…In the study conducted by Kartal, Karakas and Kapıkıran (2023), a difference was found between the variables of education level, but no difference was found between the variables of age and gender. In the study conducted by Yeşildağ, Ağırbaş, and Yılmaz (2022), a difference was found between the variables of gender and the department they studied, while no difference was found between the variables of class regular drug use. In the study conducted by Arslan and Ergün (2022) on students, a difference was found between gender variables, but no difference was found between the variables of chronic illness status and drug use status.…”
Section: Discussionmentioning
confidence: 88%
“…Health members' educational levels should be raised, and training programs linked to the topic should be updated. The eleventh development plan of the Republic of Turkey includes raising, monitoring, and evaluating rational drug use awareness [15]. University students, particularly pharmacy students, are the future providers of antibiotics.…”
Section: Introductionmentioning
confidence: 99%